2021
DOI: 10.1002/adhm.202001689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mesenchymal Stem Cell‐Derived Paracrine Signals and Their Delivery Strategies

Abstract: Mesenchymal stem cells (MSCs) have been widely studied as a versatile cell source for tissue regeneration and remodeling due to their potent bioactivity, which includes modulation of inflammation response, macrophage polarization toward proregenerative lineage, promotion of angiogenesis, and reduction in fibrosis. This review focuses on profiling the effects of paracrine signals of MSCs, commonly referred to as the secretome, and highlighting the various engineering approaches to tune the MSC secretome. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 141 publications
1
87
0
Order By: Relevance
“…Concomitant with these results, Motegi and Ishikawa 2017 [ 88 ] revealed that intradermal or intravenous administration of MSC-enriched cutaneous wound healing of acute and chronic skin injuries, for example, diabetic ulcers, acute excisional and incisional wounds, radiation ulcers, and burns in animals and humans. In animal models, the exogenous application of MSCs by topical and/or subcutaneous injection into incisional full-thickness wounds in normal or diabetic animals revealed speeding up of wound healing associated with increased reepithelization, angiogenesis, and decreased inflammation in the wounds [ 89 ]. Sorrell and Caplan 2010 [ 90 ] suggested two core mechanisms of wound healing acceleration by MSCs: (I) paracrine communication with resident cells in the wounds, infiltrating inflammatory cells, and antigen-presenting cells through the release of cytokines, growth factors, and ECM; and (II) their differentiation into resident EPSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with these results, Motegi and Ishikawa 2017 [ 88 ] revealed that intradermal or intravenous administration of MSC-enriched cutaneous wound healing of acute and chronic skin injuries, for example, diabetic ulcers, acute excisional and incisional wounds, radiation ulcers, and burns in animals and humans. In animal models, the exogenous application of MSCs by topical and/or subcutaneous injection into incisional full-thickness wounds in normal or diabetic animals revealed speeding up of wound healing associated with increased reepithelization, angiogenesis, and decreased inflammation in the wounds [ 89 ]. Sorrell and Caplan 2010 [ 90 ] suggested two core mechanisms of wound healing acceleration by MSCs: (I) paracrine communication with resident cells in the wounds, infiltrating inflammatory cells, and antigen-presenting cells through the release of cytokines, growth factors, and ECM; and (II) their differentiation into resident EPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The SDF-1 secreted from MSCs induces the survival of vascular endothelial cells, promotes vascular branching, and pericyte recruitment. These paracrine effects of MSCs play essential roles in angiogenesis rather than their direct differentiation to endothelial cells and/or pericytes [ 89 ]. In addition, some studies have revealed that angiogenic factors like VEGF, angiopoietins, and hepatic growth factor, which are released from injured tissue assist the recruitment of MSCs to the wound site [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), a group of multi-potential stem cells exhibit self-renewal and tissue differentiation ability, are capable of differentiating into endodermal, mesodermal, ectodermal, and other cell populations in vivo and in vitro [ 9 , 10 ]. In addition to bone marrow, MSCs are also derived from fat, umbilical cord blood, peripheral blood, placenta, skin, amniotic fluid, synovial membrane, teeth root, and other tissues [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that the therapeutic benefits of MSCs are principally mediated via paracrine roles, through the secretion of growth factors, chemokines, and cytokines rather than their differential abilities or cellular replacements [5,10,[44][45][46][47][48][49][50][51][52][53]. Therefore, researchers are increasingly interested in the therapeutic value of MSC-derived bioactive molecules, especially the secretome and extracellular vesicles (EVs), which are considered the key components of paracrine effect in the treatment of MSC-based therapy [54][55][56].…”
Section: Introductionmentioning
confidence: 99%